Pengaruh Literasi Kewirausahaan, Locus Of Control, Self Efficacy, Kepribadian Entrepreneurship Terhadap Intensi Berwirausaha Mahasiswa FEB UPGRIS - Fatmaningrum, Arini; Sutrisno; Sijabat, Rauly (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This research aims to examine the influence of Entrepreneurial Literacy, Locus of Control, Self Efficacy, Entrepreneurial Personality on the Entrepreneurial Intentions of FEB UPGRIS Students. This type of research uses quantitative research with primary data sources. This research used a sample of 305 respondents representing FEB UPGRIS students. The measurements for this research used a Likert scale which was processed with the help of IBM SPSS Statistics Version 26 using multiple linear regression. The research results show that: (1) Entrepreneurial Literacy has a significant effect on Students' Entrepreneurial Intentions. (2) Locus of Control has no significant effect on students' entrepreneurial intentions. (3) Self Efficacy has a significant effect on Entrepreneurial Intentions. (4) Entrepreneurship personality has a significant effect on students' entrepreneurial intentions.